LIKUIDITAS, AKTIVITAS PERUSAHAAN, LEVERAGE PADA INDEKS PENGUNGKAPAN SUSTAINABILITY REPORT : BUKTI DARI PERUSAHAAN NON-KEUANGAN - Dhistianti Mei Rachmawantari (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to examine the effect of Liquidity, Company Activity and Leverage on Sustainability Reports in Non-Financial Companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The data used in this research is quantitative data. The sampling technique using purposive sampling obtained a total sample of 104 data. Data collection with documentation and data processing with t test, f test, and test the coefficient of determination of multiple linear regression using the classical assumption test. The results of the study show that liquidity has no effect on the Sustainability Report. Company activities have a significant positive effect on sustainability report disclosure. Leverage has no effect on Sustainability Report disclosure. Liquidity, Company Activities, and Leverage affect the Sustainability Report. As for suggestions related to this research, it is hoped that readers can develop this research and add objects from various sectors so that they can provide references to investors, potential investors, and other users for making good investment decisions. It is hoped that the company can be taken into consideration by the company to further maximize and maintain the Sustainability Report in the following year.